The House of Mirth - Wharton, Edith, 1862-1937 (Salt Lake City, UT : Project Gutenberg, 1995)
"The House of Mirth" by Edith Wharton is a novel published in 1905. It follows Lily Bart, a beautiful but impoverished woman navigating New York City's high society in the 1890s. As twenty-nine-year-old Lily seeks a husband to secure her future, she faces a slow two-year social descent from privilege toward the margins of society. Wharton crafts a sharp tragedy that exposes the moral corruption of an irresponsible upper class that casually destroys what is most beautiful within it. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_House_of_Mirth
Release date is 1995-06-01
Keywords: New York (N.Y.) -- Fiction; Psychological fiction; Single women -- Fiction; Social classes -- Fiction